MAKTABGACHA YOSHDAGI BOLALARNI TA’LIM VA TARBIYALASHDA IJODKORLIK KONTSEPTSIYASI - Qodirova Nozimaxon Qaxramonjon qizi (SAMARALI TA’LIM VA BARQAROR INNOVATSIYALAR JURNALI, 2025)
This article argues that creativity is a key aspect of early childhood development and plays a crucial role in shaping children‟s thinking, problem-solving, and interaction with their world. The concept of creativity in the education and upbringing of preschool children aims to develop an environment that encourages imagination, self expression, and innovative thinking.